The assessment and development of psychosocial skills and characteristics on the male youth football (soccer) academy development pathway: a narrative review - Barraclough, J.; Grecic, D.; Harper, D. (International Journal of Sport and Exercise Psychology, 2025)
Research increasingly emphasises the importance of psychosocial skills and characteristics (PSCs) in developing academy football (soccer) players, allowing them to thrive as people and not just athletes. Empowering young people with appropriate life skills is believed to enhance chances of dealing with transitions within and outside of the academy setting. However, confusion still exists as to which PSCs are important and how to assess and develop them. Accordingly, this narrative literature review aims to (1) identify which PSCs are important, (2) evaluate current approaches to assessment and development, (3) discuss factors that affect development of PSCs within academies, and (4) propose areas for future research. Key findings were that a number of PSCs were identified to be important to deal with transitions, get an early start and develop players holistically. The review also highlights limited research investigating assessment and development in academy environments. Current assessment methods include objective tools such as questionnaires (e.g., psychological characteristics of developing excellence questionnaire) and subjective approaches such as player observations and performance profiling. Although different approaches have been advocated, the area would benefit from a more individualised, strategic and systematic approach. Future research should investigate the importance of PSCs at different ages and academy levels and the effectiveness of different approaches to integrating PSCs into curricula, including upskilling and engaging coaches into the importance of this process. It is hoped that this review will provide a stimulus for future research into the importance and effectiveness of assessing and developing PSCs in academy soccer players.